Abraham Lincoln - Mara, Wil (New York : Children's Press, 2014)
An introduction to the life of President Abraham Lincoln, who was the sixteenth president of the United States.
Includes index.
2.4
K-3
640L
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Presidents -- Biography; Biographies